A case report of spontaneous coronary artery dissection and the role of intravascular imaging for accurate diagnosis and successful management. Issue 2 (January 2019) - Chen, Chun-Chao; Liu, Ju-Chi; Sung, Li-Chin
Abstract: Rationale: Acute myocardial infarction (AMI) secondary to spontaneous coronary artery dissection (SCAD) is a rare condition. SCAD can be underdiagnosed on a coronary angiography (CAG). Therefore, the application of intravascular imaging including intravascular ultrasound (IVUS) and optical coherence tomography (OCT) is crucial for ensuring an accurate diagnosis and treatment. Patients concerns: A 72-year-old woman had an evolving AMI with ST elevation in the inferior leads (II, III, and aVF). Diagnoses: An emergent CAG showed that a double lumen had developed in the middle portion of the left circumflex artery. An IVUS examination revealed a coronary artery dissection and intramural hematoma. Interventions: First, the patient was treated with conservative management. We later placed a stent in response to the progression of the intramural hematoma observed during the IVUS follow-up. Outcomes: The patient remained symptom free after discharge. CAG with OCT at the 1-year follow-up after stent implantation showed in-stent restenosis with dissection flap with residual false lumen at the proximal site of stent. We treated this lesion with another stent. Lessons: From this case, we learned that in patients with AMI, SCAD should be considered as a possible diagnosis and that intravascular imaging tool can successfully guide clinical decision making and the treatment strategies.